Changes of the mice intestinal microbes by the oligosaccharides-enriched fermented milk in a gender-dependent pattern. (February 2021) - Wen, Jianzhu; Cao, Pei; Yang, Guo; Lan, Hangzhen; Guo, Yuxing; Zheng, Jusheng; Pan, Daodong; Wu, Zhen
Graphical abstract: Fructo-oligosaccharide (FOS), galacto-oligosaccharide (GOS) and oligomannose (MOS) were enriched in milk and fermented by Lactobacillus plantarum and tested in ICR mice model in vivo . It found that the relative abundance of several taxa were markedly different between genders at the level of phylum and genera, additionally to the changes in the microbial community. Meanwhile, the Changes of the mice intestinal microbes by the oligosaccharides-enriched fermented milk in a gender-dependent pattern. Highlights: Gender-dependent pattern exists in the mice intestinal microbes when treated with oligosaccharide enriched fermented milk. Intestinal microbes of the female mice group had significant changes when treated with the FOS enriched fermented milk. FOS has potential applications in the fermented dairy industry as a prebiotic additive. Abstract: Oligosaccharides are prebiotics that can be used to regulate microbes in the host intestine. In this study, we investigated the effects of different oligosaccharides on the changes of the intestinal microbial communities and co-related functional genes in the intestinal microbes. Fructo-oligosaccharide (FOS), galacto-oligosaccharide (GOS) and oligomannose (MOS) were enriched in milk and fermented by Lactobacillus plantarum and tested in ICR mice model in vivo . Then the changes of the fecal microbial communities were examined by 16S rDNA gene sequencing approach. We found that the relative abundance of several taxa was markedly different between genders at the level of phylum and genera, additionally to the changes in the microbial community. Meanwhile, compared with male mice, the intestinal microbes of the female mice group had significant changes. Furthermore, the intestinal microbial diversity was enhanced in the female mice when treated with the FOS enriched fermented milk. Therefore, this data suggests that oligosaccharides have the potential to improve the host microbial diversity in the intestinal tract, and FOS has potential applications in the fermented dairy industry. It revealed a gender-dependent changes of different oligosaccharides-enriched fermented milk on the intestinal microbes of mice, providing a reference for regulating the intestinal microbes by oligosaccharides.